2020
DOI: 10.4414/smw.2020.20204
|View full text |Cite
|
Sign up to set email alerts
|

Individualised nutritional support in medical inpatients – a practical guideline

Abstract: Malnutrition has been defined as a "state resulting from lack of uptake or intake of nutrition, leading to altered body composition and body cell mass, as well as to diminished physical and mental function and impaired clinical outcome from disease." Particularly for the multimorbid medical inpatient, there are multiple research studies linking malnutrition to adverse clinical outcomes independent of type of acute and chronic illnesses. Importantly, recent trials have shown that malnutrition is indeed a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…According to current literature, 30-50% of polymorbid medical inpatients are at risk for malnutrition, a condition that is strongly associated with higher mortality and morbidity, functional decline, prolonged hospital stay and increased health care costs (1)(2)(3). During hospitalization, several factors contribute to a further deterioration of nutritional status, including disease-related anorexia, immobilization as well as inflammatory and endocrine stress response (4,5). Reduced nutrients intake leads to serious protein and energy deficits, which again result in muscle wasting, impairment of muscle strength and functional capacity, respectively, in addition to increased susceptibility to complications and higher mortality (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…According to current literature, 30-50% of polymorbid medical inpatients are at risk for malnutrition, a condition that is strongly associated with higher mortality and morbidity, functional decline, prolonged hospital stay and increased health care costs (1)(2)(3). During hospitalization, several factors contribute to a further deterioration of nutritional status, including disease-related anorexia, immobilization as well as inflammatory and endocrine stress response (4,5). Reduced nutrients intake leads to serious protein and energy deficits, which again result in muscle wasting, impairment of muscle strength and functional capacity, respectively, in addition to increased susceptibility to complications and higher mortality (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…For each patient, individualized nutritional energy were defined upon hospital admission according to the weight-adjusted Harris-Benedict equation. [41,42] A recent metanalysis investigating the prediction accuracy of the predicted resting energy expenditure (REE) in healthy elderly subjects found the Mifflin equation at group level and the Harris-Benedict equation at individual level to perform best. [43] Still, the review highlights that none of the prediction equations provides accurate and precise resting energy expenditure estimates in healthy older adults and further research is thus needed to improve estimation of energy needs.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that specific formulae, generally referred to as immuno-nutrition including high amounts of arginine, glutamine, branched chain amino acids, n-3 fatty acids, and nucleotides, may provide further benefit for infection patients also including COVID-19 patients. Yet, such treatments were not studied in the EFFORT trial, nor to our knowledge, in any other trial [ [45] , [46] , [47] ]. Still, some data suggest that a diet enriched with eicosapentaenoic acid (EPA) and g-linolenic acid (GLA) may favorably reduce the pulmonary inflammatory response and support vasodilation and oxygenation in septic patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%